Real-World Utilization of Midostaurin in Combination with Intensive Chemotherapy for Patients with FLT3 Mutated Acute Myeloid Leukemia: A Multicenter Study - Secilmis, Sema; Kabukcu Hacioglu, Sibel; Hindilerden, Fehmi; Turgut, Burhan; Ozatli, Duzgun; Akgun Cagliyan, Gulsum; Altuntas, Fevzi (Mdpi, 2026)
Background/Objectives: Real-world data on the therapeutic use of FLT3 inhibitors in Turkey remain limited. Therefore, we retrospectively evaluated outcomes from 13 academic centers nationwide, focusing on the multikinase inhibitor midostaurin in patients with newly diagnosed FLT3-mutated acute myeloid leukemia (AML). Methods: We collected comprehensive information regarding treatment efficacy, safety, and tolerability. Results: The overall response rate to intensive chemotherapy (3 + 7) plus midostaurin was 87.7%, with a complete remission rate of 84.2%, consistent with previously reported clinical trial results. Treatment discontinuation due to intolerance or toxicity was low (3.5%). One patient discontinued therapy because of septic shock during induction, and another due to a drug-drug interaction during consolidation. Median overall survival was 21.4 months. Allogeneic stem cell transplantation was performed in first remission in 52.6% of patients. Five patients (8.8%) were refractory to induction therapy, and relapse occurred in 21.1% (12 patients). Conclusions: These findings support the effectiveness and acceptable tolerability of midostaurin in routine clinical practice for FLT3-mutated AML.
Keywords: acute myeloid leukemia; AML; FLT3 inhibitors; midostaurin